Tapinarof 1% Cream in Plaque Psoriasis: Mechanism of Action, Pharmacology, Clinical Efficacy, and Emerging Therapeutic Horizons — A Systematic Review - Paluszkiewicz, Natalia; Sowińska, Joanna; Bryg, Sandra; Cieślak, Aleksandra; Demkow, Sara; Leżańska, Zofia; Kwiatkowski, Mateusz; Marcinkowska, Katarzyna; Siemińska, Karolina; Pałyga, Emil (Quality in Sport, 2026)
Background. Psoriasis is a chronic, immune-mediated inflammatory dermatosis characterized by the hyperproliferation of keratinocytes and the formation of erythematous, scaly plaques. Traditional topical therapies, primarily corticosteroids and vitamin D analogs, are often limited by long-term safety concerns, such as skin atrophy. Tapinarof, a first-in-class, non-steroidal, small-molecule therapeutic agent that modulates the aryl hydrocarbon receptor (AhR), has recently emerged as a novel topical intervention. Aim. This paper evaluates the clinical efficacy, safety profile, and unique mechanism of action of tapinarof cream, 1%, for the treatment of plaque psoriasis in adults. Materials and Methods. A comprehensive review of the PSOARING 1 and PSOARING 2 Phase III clinical trials was conducted. Data were synthesized to assess primary endpoints, specifically the Physician’s Global Assessment (PGA) success—defined as a score of "clear" (0) or "almost clear" (1) with a minimum 2-grade improvement from baseline. Results. Clinical data demonstrate that tapinarof 1% cream, administered once daily, significantly improves Psoriasis Area and Severity Index (PASI) scores and PGA success compared to vehicle controls. Notably, tapinarof exhibits a unique "remittive effect," maintaining clinical response for a median of four months post-discontinuation. While generally well-tolerated, the most frequently reported adverse events include localized folliculitis and contact dermatitis, which were typically mild to moderate in severity. Conclusions. Tapinarof 1% cream represents a significant shift in the topical management of psoriasis, offering a potent, non-steroidal alternative with a durable off-treatment effect. Its ability to modulate the AhR pathway addresses both the inflammatory cascade and skin barrier dysfunction, positioning it as a foundational therapy for patients seeking long-term disease control without the risks associated with chronic corticosteroid use.